Flipped Classroom in the learning of numerical methods in civil engineering students - Asís-López, Maximiliano (2022)
There are numerous studies that point to the flipped classroom as a classroom methodology that provides benefits in the teaching-learning process, especially related to student motivationand satisfaction. This article presents the planning and application of the “Flipped Classroom” pedagogical model for teaching-learning in the course of numerical methods. During the investigation, tutorial videos were made on the course contents, which were previously prepared and then presented to the students of the Professional School of Civil Engineering of the Santiago Antúnez de Mayolo National University who were taking the subject of Numerical Methods. The students 'assessment and the possible impact of this methodology on the students' qualification was analyzed. The results obtained express that the students consider the Inverted Class as a more fun and motivating methodology than the traditional class; Furthermore, a difference is observed in  the grades obtained by the students who learned with the flipped classroom methodology and with those who did so through a traditional methodology.